72‐2: Highly Efficient Cadmium‐Free Quantum Dot Light‐Emitting Diodes Employing Top‐Emitting Architecture. Issue 1 (25th September 2020) - Park, Myoungjin; Park, Jaehong; Kim, Sungwoon; Ha, Jaekook; Lee, Changhee
Abstract : By optimizing the micro‐cavity top‐emission QD‐LED structures based on InP QDs, 3.2‐fold improvement in the efficiency is obtained compared to the bottom‐emission device structures.